Efektivitas Metode Tutor Sebaya terhadap Peningkatan Prestasi Belajar Penjumlahan dan Pengurangan Pecahan Campuran - Titik Yuliana; Azamul Fadhly Noor Muhammad (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This study aims to examine the effectiveness of the peer tutoring method in improving student achievement in the material of addition and subtraction of mixed fractions at SDN Bungkus Kretek Bantul. The peer tutoring method is an approach in which students who have a good understanding of a material help other students understand the material. The research was conducted using a quasi-experimental design. The research sample consisted of two classes at SDN Bungkus Kretek Bantul, namely an experimental class that applied the peer tutor method and a control class that applied conventional teaching methods. Data was collected through a learning achievement test which included adding and subtracting mixed fractions before and after the intervention. The results showed that there was a significant increase in learning achievement in the group of students who received the peer tutoring method. The average score of learning achievement in the experimental group increased significantly after the intervention of the peer tutor method. Whereas in the control group, the increase in learning achievement was not significant after the intervention of conventional teaching methods. This study shows that the peer tutoring method is effective in increasing the learning achievement of adding and subtracting mixed fractions. This method provides opportunities for students to learn collaboratively, help each other, and build mutual understanding. Therefore, it is suggested for teachers and schools to consider using the peer tutor method in teaching materials that are difficult for some students to understand, such as addition and subtraction of mixed fractions.